Recombinant vWF Type 2A Mutants R834Q and R834W Show a Defect in Mediating Platelet Adhesion to Collagen, Independent of Enhanced Sensitivity to a Plasma Protease - Lankhof, Hanneke; Damas, Conchi; Schiphorst, Marion E.; IJsseldijk, Martin J. W.; Bracke, Madelon; Furlan, Miha; de Groot, Philip G.; Sixma, Jan J.; Vink, Tom (Thrombosis and Haemostasis, 1999)
Type 2A von Willebrand Disease (vWD) is characterized by the absence of high molecular weight von Willebrand factor (vWF) multimers in plasma which is caused by enhanced extracellular proteolysis or defective intracellular transport. We identified in vWD type 2A patients two mutations in the A2 domain at position 834 in which arginine (R) was substituted for glutamine (R834Q) or tryptophan (R834W). We reproduced these mutations in vWF cDNA and expressed the recombinant proteins in furin cDNA containing baby hamster kidney (fur-BHK) cells. The subunit composition and the multimeric structure of both mutants was similar to wild-type (WT) vWF. Characterization of mutant R834Q by ristocetin or botrocetin induced platelet binding, and by binding to heparin showed no abnormality. R834W had normal botrocetin induced platelet binding, but ristocetin induced platelet binding and binding to heparin were decreased. Under static conditions R834Q and R834W, at 10 μg/ml, bound equally well to collagen type III as WT-vWF. At high shear rate conditions both mutants supported platelet adhesion normally when coated to a glass surface or preincubated on collagen. When R834Q or R834W was added to the perfusate, adhesion to collagen type III was 50% of the WT-vWF value, which was not due to a decreased collagen binding under flow. A divalent cation dependent protease, purified from plasma, degraded the 2A mutants rapidly while WT-vWF was not affected. In conclusion, the mutations present in the A2 domain of vWF result in an enhanced proteolytic sensitivity to a divalent ion-dependent protease. When present in the perfusate, R834Q and R834W show a decrease in platelet adhesion to collagen type III under flow conditions, which is not caused by decreased binding of the mutant vWF to collagen or enhanced proteolysis.